Controlled Power Distribution in Microresonator Chains via Concurrent Symmetry Breakings - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Del'Haye, Pascal (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We show the control of optical power patterns in coupled resonators optical waveguides (CROW) via the Kerr effect. This has applications in photonic integrated circuits, especially for light steering, sensors, and optical computing.
CRIS-Team Scopus Importer:2024-10-25